Earnings Dilution and the Explanatory Power of Earnings for Returns - Huson, Mark R.; Scott, Thomas W.; Wier, Heather A. (The Accounting Review, 2001)
Executive stock options and convertible securities can increase the number of common shares outstanding while adding less than the market value of the newly issued securities to a firm's assets. We model the effect of expected dilution on the earnings/return relation. Expected dilution effectively reduces the permanence of an earnings innovation. Empirical evidence supports the hypothesis that dilutive securities attenuate the relation between earnings and returns. Estimated earnings response coefficients (ERCs) are significantly lower when there are shares reserved for conversion. The effect is more pronounced for firms that have experienced price increases or positive earnings news, as these increase the expected dilutive effect of conversions.